Impact of mutations on the plant-based production of recombinant SARS-CoV-2 RBDs - Ruocco, Valentina; Vavra, Ulrike; König-Beihammer, Julia; Bolaños−Martínez, Omayra C.; Kallolimath, Somanath; Maresch, Daniel; Grünwald-Gruber, Clemens; Strasser, Richard (Frontiers in Plant Science, 2023)
Subunit vaccines based on recombinant viral antigens are valuable interventions to fight existing and evolving viruses and can be produced at large-scale in plant-based expression systems. The recombinant viral antigens are often derived from glycosylated envelope proteins of the virus and glycosylation plays an important role for the immunogenicity by shielding protein epitopes. The receptor-binding domain (RBD) of the SARS-CoV-2 spike is a principal target for vaccine development and has been produced in plants, but the yields of recombinant RBD variants were low and the role of the N-glycosylation in RBD from different SARS-CoV-2 variants of concern is less studied. Here, we investigated the expression and glycosylation of six different RBD variants transiently expressed in leaves of Nicotiana benthamiana. All of the purified RBD variants were functional in terms of receptor binding and displayed almost full N-glycan occupancy at both glycosylation sites with predominately complex N-glycans. Despite the high structural sequence conservation of the RBD variants, we detected a variation in yield which can be attributed to lower expression and differences in unintentional proteolytic processing of the C-terminal polyhistidine tag used for purification. Glycoengineering towards a human-type complex N-glycan profile with core α1,6-fucose, showed that the reactivity of the neutralizing antibody S309 differs depending on the N-glycan profile and the RBD variant.